Prognostic Value of Pan-Immune Inflammation Value for Major Adverse Cardiac Events and Mortality in Patients with Aortic Stenosis After TAVI - Mehmet Nail Bilen; Mehmet Rasih Sonsöz; Yusuf İnci; Yeliz Güler; Ahmet Güler; Hamdi Püşüroğlu (Medicina)
Aims: This study aimed to evaluate whether the pan-immune inflammation value (PIV) has prognostic value for major adverse cardiac events (MACEs), including stroke, rehospitalization, and in-hospital and one-year all-cause mortality, in patients with aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI). Methods: A total of 152 patients undergoing TAVI were retrospectively analyzed and stratified into two groups based on a PIV cutoff value of 488. Baseline clinical, laboratory, echocardiographic, and procedural characteristics were compared. Clinical outcomes, including mortality, cerebrovascular events, and bleeding complications, were assessed. Multivariable logistic regression and receiver operating characteristic (ROC) curve analyses were performed to identify independent mortality predictors and evaluate the predictive performance of PIV. Results: Among the 152 patients (mean age 77 ± 7 years; 59.9% female), 52 (34.2%) had a PIV ≥ 488. These patients had significantly higher rates of diabetes mellitus (62% vs. 38%, p = 0.006), chronic kidney disease (31% vs. 12%, p = 0.005), and chronic obstructive lung disease (31% vs. 15%, p = 0.022), along with higher STS scores (16.3 vs. 11.7, p = 0.003). Inflammatory markers were elevated, and lymphocyte and hemoglobin levels were reduced in the high PIV group (p < 0.001). Patients with PIV ≥ 488 experienced significantly higher one-year mortality (58% vs. 4%, p < 0.001), in-hospital mortality (21% vs. 2%, p < 0.001), rehospitalization (29% vs. 4%, p < 0.001), ischemic cerebrovascular events (12% vs. 4%, p < 0.001), and major bleeding (10% vs. 2%, p = 0.034). Multivariable analysis identified age (OR: 1.108; 95% CI: 1.010–1.217; p = 0.031) and PIV (OR: 1.006; 95% CI: 1.003–1.008; p < 0.001) as independent mortality predictors. The PIV showed a strong predictive performance (AUC: 0.90, p < 0.001), with 88% sensitivity and 81% specificity. Kaplan–Meier analysis showed significantly lower survival in the high PIV group (p < 0.001). Conclusions: A high preprocedural PIV is an independent predictor of MACEs, in-hospital, and one-year mortality in AS patients undergoing TAVI.